1757 Mass. Acts 323 - (:unkn) unknown (My University, 1757)
An Act in Addition to the Several Acts of This Province for Regulating the Militia, ch. 12: That the Captain or Chief Officer of each military foot company, shall instruct and employ his Company in military exercises six days in a year . . . and on each of said days he shall make a strict enquiry into the state of the arms and ammunition of his Company . . . that every person from the age of sixteen to sixty, not exempted by law, shall appear with arms and ammunition according to law, and attend his duty each of the aforesaid days. . .
Keywords: ARMED FORCES